Analisis Keamanan Aplikasi Dompet Digital Pendekatan Statis dan Dinamis - Gunawan, Indra (SIMETRIS, 2023)
Android application is an application or software that combines certain features in a way that is accessible to the user. The purpose of this study is to determine the level of security of the digital wallet application DANA, OVO , Go Pay, Link aja dan Shopee PAY. This digital forensic analysis uses 2 methods, namely static by using MOBSF as a network performance activity recorder application and dynamic by using Network Miner as an application to collect data about traffic on the network. The results of the research using the static method show that the five applications have dangerous permissions, while using the dynamic method shows evidence of data leakage in the digital wallet application.